Multilevel skin tissue engineering : from particulate systems to 3D functional constructs - Veiga, Anabela Alves (2024)
Skin tissue engineering (TE) is an interdisciplinary field dedicated to the development of functional constructs that can be used to re-establish, maintain, or improve the condition of injured tissue or to mimic healthy tissue. The skin-TE market is experiencing significant growth: according to Future Market Insights, a leading provider of custom and syndicated market research reports, in 2021 the global market was valued at 2.01 billion dollars and is expected to reach 4.13 billion by 2029 at an annual growth rate of 9.6%. The improvement of healthcare practices, the high technological advances, and the awareness of the need for patient-specific treatment options are some of the main market-boosting factors. The response of the scientific community to the quest for skin TE products translates into a creative landscape of multilevel and cutting-edge approaches, specific to different needs. These include 1- dimensional (1D) particles: for superficial wounds or to further incorporate in 3D matrices to improve their biological or mechanical properties; 2D gels: that can promote healing and prevent infections of superficial wounds and serve as building blocks for constructing more complex structures; and 3D constructs, namely: 3D hydrogels or 3D bioprinted structures to promote wound healing and hybrid 3D hydrogel/scaffold constructs to develop in vitro skin models. Particulate systems are characterized by a high surface area-to-volume ratio which enhances the probability of penetration and bio-interaction at the wound area. With the right particle composition, it is possible to stimulate proliferation and cell-to-cell signaling. Among these, calcium-based particles can play an important role in the healing and regeneration of skin. Calcium is essential in regulating many skin functions, including keratinocyte differentiation, skin barrier formation, and permeability barrier homeostasis. In this context, calcium phosphates (CaPs) are the most well-established source of calcium in biomedicine. They can be precipitated in mild conditions, allowing for conjugation with different molecules and polymers of interest to create bioactive hybrid formulations. CaPs and CaP/composite particles are commonly synthesized in stirred batch reactors with low micro-mixing efficiency, resulting in heterogeneous materials with a broad range of physicochemical characteristics. In that regard, oscillatory flow mixing has emerged as an alternative technology to operate under continuous mode, allowing a uniform distribution of the reaction parameters such as concentration and temperature, and leading to a product with more uniform characteristics. In this work, new CaP-based nanoparticles have been produced in continuous mode using an innovative modular oscillatory flow plate reactor (MOFPR), which allowed to obtain highly controlled and homogeneous particles with high production rates. Sericin (SS), a silk water-soluble protein with high regenerative potential and still underexplored for biomedical applications, has been co-precipitated with CaP to create new bioactive hybrid systems for tissue wound healing and regeneration. When faced with more complex needs, multi-dimensional structures can more accurately replicate the architecture and microenvironment of native tissues. In that regard, SS and silk fibroin (SF) are natural polymers that display excellent biocompatibility, versatility, and tunable properties, which outperform many natural and synthetic biomaterials. While SF has been extensively characterized in the literature, there are still several gaps in our understanding of SS. The absence of efficient extraction protocols for obtaining a “ready-to-use” SS raw material with preserved intrinsic characteristics has motivated the quest for developing a new standardized processing methodology to lay the foundation for creating 2D gels and 3D constructs including 1) crosslinked hydrogels as platforms for different skin-TE applications, 2) human skin equivalents (HSE) functionalized with CaP-based particles and 3) a bioprinted structure in which SS was used as a bioink that can produce patient-specific materials.